Operador para distribuição de soluções para algoritmos evolutivos via adaptação da matriz de covariância - Thiago Fontes Santos (2012)
This paper proposes an algorithm that works well on any number of objective functions. Our algorithm is based on a stochastic model presented in 2002 by Stefan Schaffer. Due to the deficiency of distributing this algorithm the solutions along the Pareto-optimal set, we present an operator which can solve this problem. Since we use [completar o ingles aqui] gradient method for multiobjective optimization, the cost computational is relatively low.